FeCu-HCF-atCu-HCF material as well as preparation method and application thereof
Through the core-shell design of FeCu-HCF@Cu-HCF material, the problem of poor cycling stability of Prussian blue analog in sodium ion batteries is solved, and efficient electrochemical performance and excellent rate performance are achieved.
Patent Information
- Application Number
- CN202510019329.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing Prussian blue analogs in sodium ion batteries have poor cyclic stability and low Coulomb efficiency due to structural defects and abnormal cation arrangements.
The core-shell design of FeCu-HCF@Cu-HCF material was adopted, and a square core-shell structure material with FeCu-HCF as the core and Cu-HCF as the shell was prepared through co-precipitation method and solution flow rate control technology.
It significantly improves the cycle stability and electrochemical performance of sodium ion batteries, excellent rate performance and low charge transfer resistance, ensuring the structural stability of the electrode during high rate charge and discharge.
Smart Images

Figure CN119812277A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to a FeCu-HCF@Cu-HCF material and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries have become a powerful alternative to lithium-ion batteries due to their low cost and abundant sodium resources. Among the cathode materials for sodium-ion batteries, Prussian blue analogues (PBAs) provide good sodium ion storage capacity due to their open framework structure, but their widespread structural defects and abnormal cation arrangement lead to poor cycle stability and low coulombic efficiency.
[0003] Therefore, it is of great significance to develop new cathode materials with high cycle stability and good electrochemical performance. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a FeCu-HCF@Cu-HCF material and a preparation method and application thereof. The FeCu-HCF@Cu-HCF material provided by the present invention has a special structure of a core (FeCu-HCF) and a shell (Cu-HCF), which significantly improves the cycle stability and electrochemical performance of the battery. The present invention aims to solve the volume expansion problem that Prussian blue analogs are prone to occur during repeated sodium removal / sodium insertion through a core-shell design, thereby improving the stability and conductivity of the material.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a FeCu-HCF@Cu-HCF material, comprising the following steps:
[0007] 1) mixing ferrous sulfate, sodium salt, polyvinyl pyrrolidone and water to obtain solution A;
[0008] The molar ratio of the ferrous sulfate, the molar ratio of the sodium salt, the mass of polyvinyl pyrrolidone and the volume ratio of water is 1-5 mmol: 2-10 mmol: 1 g: 50 mL;
[0009] 2) mixing sodium ferrocyanide, ascorbic acid and water to obtain solution B;
[0010] The molar ratio of the sodium ferrocyanide, the mass of ascorbic acid and the volume ratio of water is 1-5 mmol: 0.1-0.5 g: 50 mL;
[0011] 3) mixing and stirring the solution A obtained in step 1) and the solution B obtained in step 2) in equal volumes to obtain a solution C;
[0012] 4) mixing sodium ferrocyanide, polyvinyl pyrrolidone and water to obtain solution D;
[0013] The molar ratio of the sodium ferrocyanide, the mass of polyvinyl pyrrolidone and the volume ratio of water is 1-2mmol:0.3g:50mL;
[0014] 5) mixing copper chloride, sodium salt and water to obtain solution E;
[0015] The molar ratio of the copper chloride, the mass of the sodium salt and the volume ratio of water is 1-2 mmol: 0.516-1 g: 50 mL;
[0016] 6) adding the solution D obtained in step 4) and the solution E obtained in step 5) dropwise to the solution C obtained in step 3), and then stirring, aging and drying in sequence to obtain FeCu-HCF@Cu-HCF material;
[0017] The droplet rates of solution D and solution E are both 0.5 mL / min;
[0018] The drop rate of the solution C is 2 mL / min;
[0019] The volume ratio of solution D, solution E and solution C is 1:1:2.
[0020] Preferably, in step 1), the molar ratio of ferrous sulfate, the molar ratio of sodium salt, the mass of polyvinyl pyrrolidone and the volume ratio of water is 3mmol:2-10mmol:1g:50mL.
[0021] Preferably, in step 2), the molar ratio of sodium ferrocyanide, the mass of ascorbic acid and the volume ratio of water is 3 mmol: 0.1-0.5 g: 50 mL.
[0022] Preferably, the stirring time in step 3) is 12 hours.
[0023] Preferably, the sodium salt comprises sodium citrate and / or sodium pyrophosphate.
[0024] Preferably, the stirring time in step 6) is 12 hours;
[0025] The drying conditions include: vacuum drying at 120° C. for 12 hours.
[0026] The aging conditions include: aging at a temperature of 20-30° C. for 24 hours.
[0027] The present invention also provides a FeCu-HCF@Cu-HCF material prepared by the preparation method described in the above technical solution, which has a square core-shell structure with FeCu-HCF as the core and Cu-HCF as the shell.
[0028] The present invention also provides the use of the FeCu-HCF@Cu-HCF material described in the above technical solution as a positive electrode material for a sodium ion battery.
[0029] The present invention also provides the use of the FeCu-HCF@Cu-HCF material described in the above technical solution in improving the cycle stability of the positive electrode material of a sodium ion battery.
[0030] The present invention also provides the use of the FeCu-HCF@Cu-HCF material described in the above technical solution in improving the rate performance of the positive electrode material of a sodium ion battery.
[0031] Beneficial effects of the present invention:
[0032] 1. The material has a square core-shell structure
[0033] The present invention adopts a coprecipitation method and adjusts the flow rate of the solution to obtain a square-shaped core-shell composite material (FeCu-HCF@Cu-HCF) with FeCu-HCF as the core and Cu-HCF as the shell. This structure can effectively optimize the microstructure of the material, enhance the synergistic effect of the core and the shell, and ensure the structural integrity of the material during repeated sodium insertion and extraction, thereby effectively improving the stability and cycle performance of the material.
[0034] 2. Process technology for controlling material morphology (core-shell structure) by solution flow rate
[0035] By precisely controlling the titration rate and solution concentration in the process of the present invention, the precise concentration distribution of the Cu element in the core (FeCu-HCF) and shell (Cu-HCF) layers can be achieved. The controllability of this ratio ensures that the core-shell structure material has a uniform element distribution during the synthesis process, avoids the instability of electrochemical performance caused by uneven composition, and provides theoretical support for further optimizing the electrochemical properties of the material.
[0036] 3. The material has excellent electrochemical cycle-rate performance
[0037] As a positive electrode material for sodium-ion batteries, FeCu-HCF@Cu-HCF material exhibits excellent rate performance and cycle stability. Under high current density conditions, the material can still maintain a stable specific capacity, showing low charge transfer resistance and high sodium ion diffusion coefficient, which is attributed to the core-shell structure effectively alleviating the volume expansion problem and ensuring the rapid ion transport and structural stability of the electrode during high-rate charge and discharge. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.
[0039] Figure 1 It is a process schematic diagram of the present invention;
[0040] Figure 2 is an XRD comparison diagram of Example 4 of the present invention; wherein, in the abscissa 2θ, θ represents the diffraction angle of X-ray diffraction, and the ordinate Intensity represents the diffraction intensity;
[0041] Figure 3 is a SEM image of Example 4 of the present invention;
[0042] Figure 4 : is a long cycle diagram of Example 4 of the present invention at a current density of 0.5C; wherein the abscissa Cycle Number is the number of cycles, and the ordinate Specific Capacity represents the specific capacity;
[0043] Figure 5 is a rate diagram of Example 4 of the present invention, wherein the abscissa Cycle Number is the number of cycles, and the ordinate Specific Capacity represents the specific capacity;
[0044] Figure 6 is a charge-discharge cycle diagram of Example 4 of the present invention, wherein the abscissa Specific Capacity represents the specific capacity, and the ordinate Voltage represents the cycle voltage;
[0045] Figure 7 It is a CV diagram of Example 4 of the present invention, wherein the horizontal axis Potential represents the potential and the vertical axis Current represents the current. DETAILED DESCRIPTION
[0046] The present invention provides a method for preparing a FeCu-HCF@Cu-HCF material, comprising the following steps:
[0047] 1) mixing ferrous sulfate, sodium salt, polyvinyl pyrrolidone and water to obtain solution A;
[0048] The molar ratio of the ferrous sulfate, the molar ratio of the sodium salt, the mass of polyvinyl pyrrolidone and the volume ratio of water is 1-5 mmol: 2-10 mmol: 1 g: 50 mL;
[0049] 2) mixing sodium ferrocyanide, ascorbic acid and water to obtain solution B;
[0050] The molar ratio of the sodium ferrocyanide, the mass of ascorbic acid and the volume ratio of water is 1-5 mmol: 0.1-0.5 g: 50 mL;
[0051] 3) mixing and stirring the solution A obtained in step 1) and the solution B obtained in step 2) in equal volumes to obtain a solution C;
[0052] 4) mixing sodium ferrocyanide, polyvinyl pyrrolidone and water to obtain solution D;
[0053] The molar ratio of the sodium ferrocyanide, the mass of polyvinyl pyrrolidone and the volume ratio of water is 1-2mmol:0.3g:50mL;
[0054] 5) mixing copper chloride, sodium salt and water to obtain solution E;
[0055] The molar ratio of the copper chloride, the mass of the sodium salt and the volume ratio of water is 1-2 mmol: 0.516-1 g: 50 mL;
[0056] 6) adding the solution D obtained in step 4) and the solution E obtained in step 5) dropwise to the solution C obtained in step 3), and then stirring, aging and drying in sequence to obtain FeCu-HCF@Cu-HCF material;
[0057] The droplet rates of solution D and solution E are both 0.5 mL / min;
[0058] The drop rate of the solution C is 2 mL / min;
[0059] The volume ratio of solution D, solution E and solution C is 1:1:2.
[0060] The present invention mixes ferrous sulfate, sodium salt, polyvinyl pyrrolidone and water to obtain solution A; the mole of ferrous sulfate, the mole of sodium salt, the mass of polyvinyl pyrrolidone and the volume ratio of water are 1-5mmol:2-10mmol:1g:50mL. In the present invention, the mole of ferrous sulfate, the mole of sodium salt, the mass of polyvinyl pyrrolidone and the volume ratio of water are preferably 3mmol:2-10mmol:1g:50mL. In the present invention, the sodium salt preferably includes sodium citrate and / or sodium pyrophosphate.
[0061] The invention mixes sodium ferrocyanide, ascorbic acid and water to obtain solution B; the mole ratio of the sodium ferrocyanide, the mass of the ascorbic acid and the volume ratio of the water is 1-5 mmol: 0.1-0.5 g: 50 mL.
[0062] In the present invention, the obtained solution A and the obtained solution B are mixed and stirred in equal volumes to obtain solution C. In the present invention, the stirring time is preferably 12 hours. In the present invention, the solution A is preferably added dropwise to the solution B, and the dropping speed is preferably 2 ml / min.
[0063] The present invention mixes sodium ferrocyanide, polyvinyl pyrrolidone and water to obtain a solution D; the mole ratio of the sodium ferrocyanide, the mass of the polyvinyl pyrrolidone and the volume ratio of the water is 1-2mmol:0.3g:50mL.
[0064] The present invention mixes copper chloride, sodium salt and water to obtain solution E; the mole ratio of the copper chloride, the mass of the sodium salt and the volume ratio of the water is 1-2 mmol: 0.516-1 g: 50 mL.
[0065] In the present invention, the obtained solution D and the obtained solution E are added dropwise to the obtained solution C, and then stirred, aged and dried in sequence to obtain FeCu-HCF@Cu-HCF material; the dropping rate of the solution D and the solution E is 0.5 mL / min; the dropping rate of the solution C is 2 mL / min; the volume ratio of the solution D, solution E and solution C is 1:1:2. In the present invention, the stirring time is preferably 12 hours. In the present invention, the drying conditions preferably include: vacuum drying at a temperature of 120°C for 12 hours. In the present invention, the aging conditions preferably include: aging at a temperature of 20 to 30°C for 24 hours.
[0066] The present invention also provides a FeCu-HCF@Cu-HCF material prepared by the preparation method described in the above technical solution, which has a square core-shell structure with FeCu-HCF as the core and Cu-HCF as the shell.
[0067] The present invention also provides the use of the FeCu-HCF@Cu-HCF material described in the above technical solution as a positive electrode material for a sodium ion battery.
[0068] The present invention also provides the use of the FeCu-HCF@Cu-HCF material described in the above technical solution in improving the cycle stability of the positive electrode material of a sodium ion battery.
[0069] The present invention also provides the use of the FeCu-HCF@Cu-HCF material described in the above technical solution in improving the rate performance of the positive electrode material of a sodium ion battery.
[0070] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0071] Example 1
[0072] 5 mmol FeSO 4 7H 2 O, 10 mmol sodium citrate and 1 g polyvinyl pyrrolidone (PVP) were dissolved in 50 ml deionized water to form solution A;
[0073] 5mmol Na 4 Fe(CN) 6 10H 2 O and 0.5 g ascorbic acid (VC) were dissolved in 50 mL of deionized water to form solution B;
[0074] Under stirring conditions, solution A was added to solution B at 2 ml / min through a burette. After the addition was completed, the solution turned into a dark blue suspension. Stirring was continued at room temperature for 12 h to obtain solution C, i.e., FeCu-HCF solution.
[0075] Prepare 50 mL of deionized water containing 1 mmol Na 4 Fe(CN) 6 10H 2 O and 0.3 g polyvinyl pyrrolidone (PVP) as solution D;
[0076] 1mmol CuCl 2 Solution E: 0.516 g of sodium citrate was dissolved in 50 mL of deionized water;
[0077] Solution E and solution D were titrated into solution C simultaneously under stirring. The dropping rate of solution D and solution E was 0.5 mL / min. The dropping rate of solution C was 2 mL / min.
[0078] The mixture was stirred at room temperature for 12 h and aged at room temperature for 24 h.
[0079] After discarding the supernatant, the white precipitate below was washed several times with deionized water and anhydrous ethanol by centrifugation, and then dried in vacuum at 120°C for 12 h to obtain a core-shell structured positive electrode material with copper-doped Prussian blue as the core and copper Prussian blue as the shell, marked as FeCu-HCF@Cu-HCF.
[0080] Example 2
[0081] 1 mmol FeSO 4 7H 2 O, 2mmol sodium pyrophosphate and 1g polyvinylpyrrolidone (PVP) were dissolved in 50ml deionized water to form solution A;
[0082] 1mmol Na 4 Fe(CN) 6 10H 2 O and 0.1 g ascorbic acid (VC) were dissolved in 50 ml of deionized water to form solution B;
[0083] Under stirring conditions, solution A was added to solution B through a burette at the same time. After the addition was completed, the solution turned into a dark blue suspension. Stirring was continued at room temperature for 12 hours to obtain solution C.
[0084] Prepare 50 mL of deionized water containing 1 mmol Na 4 Fe(CN) 6 10H 2O and 0.3 g polyvinyl pyrrolidone (PVP) as solution D;
[0085] 1mmol CuCl 2 Solution E: 0.516 g of sodium pyrophosphate was dissolved in 50 mL of deionized water;
[0086] Solution E and solution D were titrated into solution C under stirring. The dropping rate of solution D and solution E was 0.5 mL / min. The dropping rate of solution C was 2 mL / min.
[0087] The mixture was stirred at room temperature for 12 h and aged at room temperature for 24 h.
[0088] After discarding the supernatant, the white precipitate below was washed several times with deionized water and anhydrous ethanol by centrifugation, and then dried in vacuum at 120°C for 12 h to obtain a core-shell structured positive electrode material with copper-doped Prussian blue as the core and copper Prussian blue as the shell, marked as FeCu-HCF@Cu-HCF.
[0089] Example 3
[0090] 3 mmol FeSO 4 7H 2 O, 10 mmol sodium pyrophosphate and 1 g polyvinyl pyrrolidone (PVP) were dissolved in 50 ml deionized water to form solution A;
[0091] 3mmol Na 4 Fe(CN) 6 10H 2 O and 0.1 g ascorbic acid (VC) were dissolved in 50 ml of deionized water to form solution B;
[0092] Under stirring conditions, solution A was added to solution B through a burette at the same time. After the addition was completed, the solution turned into a dark blue suspension. Stirring was continued at room temperature for 12 hours to obtain solution C.
[0093] Prepare 50 mL of deionized water containing 1 mmol Na 4 Fe(CN)6·10H 2 O and 0.3 g polyvinyl pyrrolidone (PVP) as solution D;
[0094] 1mmol CuCl 2 Solution E: 0.516 g of sodium pyrophosphate was dissolved in 50 mL of deionized water;
[0095] Solution E and solution D were titrated into solution C under stirring. The dropping rate of solution D and solution E was 0.5 mL / min. The dropping rate of solution C was 2 mL / min.
[0096] The mixture was stirred at room temperature for 12 h and aged at room temperature for 24 h.
[0097] After discarding the supernatant, the white precipitate below was washed several times with deionized water and anhydrous ethanol by centrifugation, and then dried in vacuum at 120°C for 12 h to obtain a core-shell structured positive electrode material with copper-doped Prussian blue as the core and copper Prussian blue as the shell, marked as FeCu-HCF@Cu-HCF.
[0098] Example 4
[0099] 3 mmol FeSO 4 7H 2 O, 10 mmol sodium pyrophosphate and 1 g polyvinyl pyrrolidone (PVP) were dissolved in 50 ml deionized water to form solution A;
[0100] 3mmolNa 4 Fe(CN) 6 10H 2 O and 0.1 g ascorbic acid (VC) were dissolved in 50 ml of deionized water to form solution B;
[0101] Under stirring conditions, solution A was added to solution B through a burette at the same time. After the addition was completed, the solution turned into a dark blue suspension. Stirring was continued at room temperature for 12 hours to obtain solution C.
[0102] Prepare 50 mL of deionized water containing 2 mmol Na 4 Fe(CN) 6 10H 2 O and 0.3 g polyvinyl pyrrolidone (PVP) as solution D;
[0103] 2mmol CuCl 2 Solution E: 1 g of sodium pyrophosphate was dissolved in 50 mL of deionized water;
[0104] Solution E and solution D were titrated into solution C under stirring. The dropping rate of solution D and solution E was 0.5 mL / min. The dropping rate of solution C was 2 mL / min.
[0105] The mixture was stirred at room temperature for 12 h and aged at room temperature for 24 h.
[0106] After discarding the supernatant, the white precipitate below was washed several times with deionized water and anhydrous ethanol by centrifugation, and then dried in vacuum at 120°C for 12 h to obtain a core-shell structured positive electrode material with copper-doped Prussian blue as the core and copper Prussian blue as the shell, marked as FeCu-HCF@Cu-HCF.
[0107] Comparative Example 1
[0108] 5 mmol FeSO 4 7H 2 O, 10 mmol sodium pyrophosphate and 1 g polyvinyl pyrrolidone (PVP) were dissolved in 50 ml deionized water to form solution A;
[0109] 5mmol Na4Fe(CN)6·10H 2 O and 0.5 g ascorbic acid (VC) were dissolved in 50 ml of deionized water to form solution B;
[0110] Under stirring conditions, solution A was added to solution B through a burette at the same time. After the addition was completed, the solution turned into a dark blue suspension. Stirring was continued at room temperature for 12 hours, and finally aged at room temperature for 24 hours.
[0111] After the supernatant was poured off, the white precipitate below was washed several times with deionized water and anhydrous ethanol by centrifugation and then dried in vacuum at 120°C for 12 h to obtain a copper-doped Prussian blue positive electrode material, which was labeled as FeCu-HCF.
[0112] The obtained FeCu-HCF positive electrode material was mixed with superconducting carbon black and polyvinylidene fluoride (PVDF) in a molar ratio of 6.5:2.5:1 to form a slurry, which was then coated on aluminum foil and dried, punched and pressed to form a positive electrode material electrode. Metal sodium was used as the counter electrode, Grade GF / C was used as the separator, and 1M NaClO containing 2wt.% FEC was used. 4 / (EC+DMC+EMC)(EC:DMC:EMC=1:1:1) is the electrolyte to assemble the battery for constant current charge and discharge test, and the voltage range is between 2.0~4.2V.
[0113] The battery cycle performance test was conducted with a current of 0.5C and 300 cycles. The rate test current density was 0.3C-0.5C-1C-2.5C-5C-10C-0.3C. The first three cycles of the charge and discharge cycle were selected, with the horizontal axis representing the specific capacity and the vertical axis representing the cycle voltage.
[0114] In Example 1, at 0.5C, the first discharge capacity was 138.4 mAh / g, and the capacity was maintained at 94 mAh / g after 300 cycles. The capacities at currents of 0.3C-0.5C-1C-2.5C-5C-10C-0.3C were 172, 137.6, 92.3, 63.1, 37.5, and 96.4 mAh / g, respectively.
[0115] The first discharge of Example 2 at 0.5C is 116.4 mAh / g, and the capacity is maintained at 89.7 mAh / g after 300 cycles. The capacities at currents of 0.3C-0.5C-1C-2.5C-5C-10C-0.3C are 139, 117.8, 101.3, 73.1, 32.5, and 82.4 mAh / g, respectively.
[0116] The first discharge of Example 3 at 0.5C is 132.4 mAh / g, and the capacity is maintained at 92.6 mAh / g after 300 cycles. The capacities at currents of 0.3C-0.5C-1C-2.5C-5C-10C-0.3C are 154, 121.6, 92.3, 73.1, 41.5, and 92.7 mAh / g, respectively.
[0117] Figure 3 This is the SEM picture of Example 4 of the present invention, and the morphology is micron-scale square flakes.
[0118] Figure 4 For the cycle comparison between Example 4 and the comparative example, the first discharge of FeCu-HCF@Cu-HCF was 130.1 mAh / g, and the capacity was maintained at 101 mAh / g after 300 cycles. The first discharge of FeCu-HCF was 147.9 mAh / g, and the retention was 83 mAh / g after 100 cycles.
[0119] Figure 5 For the rate performance comparison between Example 4 and the comparative example, the capacities of FeCu-HCF@Cu-HCF and FeCu-HCF at currents of 0.3C-0.5C-1C-2.5C-5C-10C-0.3C are 169.7, 119.5, 94.6, 68.4, 22.9, 0.1, 96.9 mAh / g and 130.2, 120.8, 108.1, 96, 74.8, 47.4, 103.6 mAh / g, respectively.
[0120] Figure 6 The first three charge and discharge cycles of Example 4 of the present invention are shown, and the discharge voltage platforms are 3.5V and 2.65V.
[0121] Figure 7 is the CV diagram of Example 4 of the present invention, the redox peak is consistent with the charge and discharge voltage platform, wherein the horizontal axis Potential represents the potential, and the vertical axis Current represents the current.
[0122] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing FeCu-HCF@Cu-HCF material, characterized in that: The following steps are involved: 1) mixing ferrous sulfate, sodium salt, polyvinyl pyrrolidone and water to obtain solution A; The molar ratio of the ferrous sulfate, the molar ratio of the sodium salt, the mass of polyvinyl pyrrolidone and the volume ratio of water is 1-5 mmol: 2-10 mmol: 1 g: 50 mL; 2) mixing sodium ferrocyanide, ascorbic acid and water to obtain solution B; The molar ratio of the sodium ferrocyanide, the mass of ascorbic acid and the volume ratio of water is 1-5 mmol: 0.1-0.5 g: 50 mL; 3) mixing and stirring the solution A obtained in step 1) and the solution B obtained in step 2) in equal volumes to obtain a solution C; 4) mixing sodium ferrocyanide, polyvinyl pyrrolidone and water to obtain solution D; The molar ratio of the sodium ferrocyanide, the mass of polyvinyl pyrrolidone and the volume ratio of water is 1-2mmol:0.3g:50mL; 5) mixing copper chloride, sodium salt and water to obtain solution E; The molar ratio of the copper chloride, the mass of the sodium salt and the volume ratio of water is 1-2 mmol: 0.516-1 g: 50 mL; 6) adding the solution D obtained in step 4) and the solution E obtained in step 5) dropwise to the solution C obtained in step 3), and then stirring, aging and drying in sequence to obtain FeCu-HCF@Cu-HCF material; The droplet rates of solution D and solution E are both 0.5 mL / min; The drop rate of solution C is 2 mL / min; The volume ratio of solution D, solution E and solution C is 1:1:
2.
2. The preparation method according to claim 1, characterized in that: In the step 1), the molar ratio of ferrous sulfate, the molar ratio of sodium salt, the mass of polyvinyl pyrrolidone and the volume ratio of water is 3mmol:2-10mmol:1g:50mL.
3. The preparation method according to claim 1, characterized in that: In the step 2), the molar ratio of sodium ferrocyanide, the mass of ascorbic acid and the volume ratio of water is 3mmol:0.1-0.5g:50mL.
4. The preparation method according to claim 1, characterized in that: The stirring time in step 3) is 12 hours.
5. The preparation method according to claim 1, characterized in that: The sodium salt includes sodium citrate and / or sodium pyrophosphate.
6. The preparation method according to claim 1, characterized in that: The stirring time of step 6) is 12h; The drying conditions include: vacuum drying at 120°C for 12h; The aging conditions include: aging at a temperature of 20-30° C. for 24 hours.
7. A FeCu-HCF@Cu-HCF material prepared by the preparation method according to any one of claims 1 to 6, having a square core-shell structure, with FeCu-HCF as the core and Cu-HCF as the shell.
8. Use of the FeCu-HCF@Cu-HCF material according to claim 7 as a positive electrode material for sodium ion batteries.
9. Use of the FeCu-HCF@Cu-HCF material according to claim 7 in improving the cycle stability of positive electrode materials for sodium ion batteries.
10. Use of the FeCu-HCF@Cu-HCF material according to claim 7 in improving the rate performance of positive electrode materials for sodium ion batteries.